Pengembangan Aplikasi Permainan "Artifact Hunter" Berbasis Design Play Experience (DPE) Framework - Septian Pratama Widianto; Wibisono Sukmo Wardhono; Tri Afirianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Cultural heritage is a product of tradition and spiritual achievement of the past as the identity of a nation, one example of cultural heritage are artifacts. As a culturally rich nation, Indonesians often ignore the existing cultural heritage, as people assume that the cultural heritage is irrelevant to modern times, whereas cultural heritage has an important role to play in establishing national identity. Based on the above problems, then designed a serious game as a medium of educational information on cultural heritage in the form of artifacts. The design of a serious game applies the DPE framework that divides the design into several layers. The layers include: learning layer, storytelling layer, gameplay layer, user experience layer, and technology layer. Tests conducted on the design of this serious game are black box testing, usability testing and paired t-test. Black box testing is used to determine the functional requirements, usability testing is used to determine the user response, and paired t-test is used to determine the effectiveness of the game designed about whether user's knowledge is increased or not about cultural heritage in the form of artifacts. From the results of tests conducted, it can be concluded that the serious game designed already fulfilled the learning objectives and fun factors as the essence of the game.